Relationship between filter cigarettes smoking habits with the appearance of smoker’s melanosis (Observation of smoking duration and the amount of cigarettes consumption) - Akbar, Rizal Rizky; Widyaputra, Sunardhi; Kintawati, Silvi (Universitas Padjadjaran, 2014)
Introduction: Smoking is one of bad habits that are difficult to abandon. Cigarettes contain more than 59 known carcinogenic substances. Cigarettes also contain some metal components and free radicals. Cigarettes consist of several types, one of which is cigarettes filter, which is the most frequently consumed cigarettes. One of the adverse effects of cigarette smoker’s melanosis is a pigmentation disorder that appears in oral cavity. The study aims to look at the relationship between smoking habits of filter’s smoker with appearance of smoker’s melanosis. Methods: This was a descriptive analytic with chi-square test to analyze the relationship between smoking in filter smokers with appearance of smoker’s melanosis. The samples were 90 students of the Faculty of Geology University of Padjadjaran. The smokers who have the criteria of the sample are examined to see the oral condition whether there is a melanosis lesion or not. Results: The result showed an association between smoking habit in filter smokers with the onset of smokers melanosis that observe through the duration of smoking and the amount of cigarettes consumption. Conclusion: There is a relationship between smoking habits in filter smokers and the onset of smoker’s melanosis in terms of smoking duration and the number of cigarettes consumed.